Conveying the Meaning through Experiential Metafunction on Song Lyrics: A Case on Ideational Metafunction - Sinaga, Yanti Kristina; Murni Situmorang, Natalia; Purba, Elprinawati; Sitompul, Heppy Theresia; Panjaitan, Anita; Herman, Herman; Thao, Nguyen Van (Anglophile Journal, 2023)
This research explores the song "Better Man" by Westlife to uncover its experiential meaning and how it impacts the audience. Using the Systemic Functional Linguistics (SFL) framework, the study analyzes the song's meaning by examining the processes, participants, and circumstances in the lyrics. Qualitative content analysis is employed to identify various emotional experiences expressed through language. The study involves deconstructing each sentence to understand how participants, processes, and circumstances are used in the song. The primary data source is the authentic lyrics from reliable sources like official songbooks and verified lyric websites to ensure accuracy. The SFL theory helps examine experiential meta function and its components in the lyrics, considering the entire complexity of language in social contexts. The analysis reveals that "Better Man" predominantly employs mental processes, reflecting the singer's personal thoughts and perspectives. The use of verbs like "love," "say," and "hidden" effectively conveys emotions and interactions between individuals. The song's participants, such as "better man" and "her," create emotional connections with listeners. The findings emphasize the importance of language as an expressive tool in art and music, guiding songwriters in effectively communicating deeper messages and meanings. Song lyrics, with their emotional storytelling, establish powerful connections with the audience. While this study offers valuable insights into "Better Man," there is potential for further research. Analyzing more songs and genres can deepen the understanding of how language conveys experiences and emotions in music's broader context. Keywords: Experiential Metafunction, Systemic Functional Linguistics, Ideational Metafunction